Sense of Personal Control Intensifies Moral Judgments of Others’ Actions - Cornwell, James F. M.; Higgins, E. Tory (Frontiers in Psychology, 2019)
Recent research in moral psychology has highlighted how the current internal states of observers can influence their moral judgments of others’ actions. In this article, we argue that an important internal state that serves such a function is the sense of control one has over one’s own actions. Across four studies, we show that an individual’s own current sense of control is positively associated with the intensity of moral judgments of the actions of others. We also show that this effect extends not only to judgments of rightness and wrongness (Study 1), but also to assignments of reward and punishment (Study 2). Finally, we demonstrate that this effect is based on the current experience of control by showing a moderation of the effect via motivational states (promotion; prevention) that either lead one to incorporate or disregard internal states when making judgments (Study 3) and by subtly manipulating participants’ sense of control (Study 4).